Perjanjian Kerjasama Antara PT. Pelabuhan Indonesia I (Persero) Belawan Internasional Container Terminal (BICT) Dengan PT. Prima Indonesia Logistik Tentang Kerjasama Pengelolaan dan Pengoperasian Peralatan Reach Stacker di Terminal BICT - NOVIZA AMALIA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Suhaidi, SH, MH2.  Dr. Sutiarnoto, SH, MHum3.  Dr. Jelly Leviza, SH, MHum The mechanism of making the design of cooperative agreement between PT Pelindo I of Belawan International Container Terminal (BICT) and PT. Prima Indonesia Logistic on cooperation in Managing and Operating Reach Stacker at BICT terminal is made based on negotiation. This agreement should meet the requirements as stipulated in Article 1320 of the Civil Code, and its implementation does not give any balance between right and obligation since the First Party has more portion of right than the Second Party, while it has less responsibility than the Second Party does. In practice, the clause of the agreement which often makes the Second Party default is about “providing backup device at least 1x24 (one times twenty four) hours when there is damage which can cause the delay in lift on/lift off service or one day after it damages, and all costs will be imposed on the Second Party.” In reality, the repairmen cannot be done in 24 hours plus the absence of backup device. In consequence, receiving and delivery activities cannot be served.Keywords: Cooperative Agreement, Reach Stacker.